Heron's Cove [large type] - Neggers, Carla (Neggers, Carla. Sharpe & Donovan novel., 2012)
FBI art-crimes expert Emma Sharpe and deep-cover agent Colin Donovan are recuperating in Heron's Cove when they learn of a rare set of Russian jewelry that's about to be stolen. Their best chance of stopping the theft is splitting up, but with a powerful enemy lurking in the shadows, can Emma and Colin cheat death and be reunited a second time?